Engaging Mind: The Art of Teacher Talk In Efl Classroom - Rohmawati, Aidah; Hidayani, Selnistia; Oktaviani , Fadilla (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This research investigates the critical role of teacher talk in enhancing student engagement and comprehension in English as a Foreign Language (EFL) classroom. Through qualitative methods, including observations, interviews, and documentation at SDIT Widya Cendekia, the study examines the communication strategies employed by teachers to create an interactive learning environment. Findings reveal that effective teacher talk incorporates various interactive features such as scaffolding, questioning techniques, and the use of multimedia resources, which actively involve students and facilitate language acquisition. The results also indicate that the teacher must maintain a dynamic classroom environment conducive to questioning and surveying while changing her style of communication to facilitate the educational process. This study speaks directly to how the teacher can optimize teacher talk in order to create the desired learning outcomes in the EFL context by stating best practices to engage students and support language development.